2016
DOI: 10.15740/has/fsrj/7.1/105-111
|View full text |Cite
|
Sign up to set email alerts
|

Standardization, chemical characterization and storage studies on Metkut, a pulse based Indian traditional food adjunct

Abstract: Metkut, a dry chutney powder is an adjunct in the Maharashtrian (a western region of India) cuisine. The formulation and process parameters of metkut were standardized with bengal gram (50%), dehulled black gram (24%), rice (12.5%), spice mix (11.5%) and turmeric powder (2%) with the roasting temperature of 150 0 C . The product was found to be rich in protein (20.42%) and carbohydrates (67.86 %). The net dietary protein calorie per cent (NDPCal %) was 10.06 per cent indicating the product's use as a protein s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The changes may be contributed to the increase in non-enzymatic browning and decrease in carotenoids upon exposure to light during storage [27].The changes in colour units had significant effect on the quality of the product. Rao, et al [28] also observed the effect of colour changes measured using Lovibond Tintometer on the quality of tomato powder and instant tomato pickle mix while Khedkaret al [29] studied the effect of storage on colour for metkut, an pulse based food adjunct. IV.…”
Section: Moisture Sorption Isothermmentioning
confidence: 99%
“…The changes may be contributed to the increase in non-enzymatic browning and decrease in carotenoids upon exposure to light during storage [27].The changes in colour units had significant effect on the quality of the product. Rao, et al [28] also observed the effect of colour changes measured using Lovibond Tintometer on the quality of tomato powder and instant tomato pickle mix while Khedkaret al [29] studied the effect of storage on colour for metkut, an pulse based food adjunct. IV.…”
Section: Moisture Sorption Isothermmentioning
confidence: 99%